FAKTOR RISIKO KONDISI LINGKUNGAN FISIK RUMAH DENGAN PENDERITA TB PARU - Samuel Marganda Halomoan Manalu; Deli Syaputri; Tisnawati Tanjung; Theodorus Teddy Bambang Soedjadi (Poltekkes Kemenkes Medan, 2022)
The results of survey on prevalence of TB in Indonesia in 2013-2014 from bacteriological confirmation in the population aged 15 years and over produced; The prevalence of smear-positive pulmonary tb per 1000.000 population aged 15 years and over is 257 (with a 95% confidence level 210-303), The prevalence of pulmonary tbwith bacteriological confirmation per 100.000 population aged 15 years and over is 759 (with 95% confidence interval 590-961), The prevalence of bacteriologically confirmed pulmonary tb at all ages per 100.000 population was 601 (with 95% confidence interval 466-758), and the prevalence of tb of all forms for all ages per 100.000 population is 660 (with a 95% confidence interval 523-813), it is estimated that there are 1.600.000 (with a confidence interval of 1.300.000-2.000.000) people with tb in Indonesia (Kepmenkes, 2015). The characteristics of a healthy house in question include; adequate ventilation, lighting, occupancy density, and humidity. The purpose of this study was to determine the relationship between the physical environment of the house and the incidence of pulmonary tb in Tiga Panah Disctrict, Karo Regency. Observational research with case control design. Cases are patients with pulmonary tb. Controls were non pulmonary tb patients. Samples were taken by simple random sampling as many 60 cases and 60 controls. Where the researchers measured the dependent variable first, while the independent variable was retrospectively to determine whether there was a risk of pulmonary tb incidence. Statistical test used was Chi-Square (bivariate analysis). The results showed that occupancy density, ventilation area, floor conditions, and lighting were risk factors for pulmonary tb. Occupancy density variable is the most dominant variable with the incidence of pulmonary tb with OR value 0.328 CI 0.154-0.695, p value 0.006. for this reason, Puskesmas Tiga Panah and Dinas Kesehatan Kabupaten Karo increase public knowledge about the area needed for each house to prevent pulmonary tb.